Response of wildlife communities to human activities in the distribution area of the North China Leopard - Mengyan Zhu; Yue Zhao; Meng Wang; Muhammad Zaman; Guangshun Jiang (Global Ecology and Conservation, 2024)
Currently, human activities are among the most important factors affecting the distribution of wildlife, and conservationists around the world are working to uncover the true impact of human activities on wildlife. With the rapid disappearance of tigers and wolves in North China in recent decades, leopards have become the only top predators. However, the responses of wildlife, including leopards, to human activities in North China leopard distribution areas remain unknown. This study systematically quantified human disturbance and village distance as gradient variables to measure the intensity of human activities, and community threshold analysis was used to analyze the threshold response of wildlife communities to human activities in the North China leopard distribution area. The results showed that human disturbance and village distance had threshold effects on the wildlife community. There were different response thresholds for 19 wildlife species, including leopards, to human activities. The findings show that reasonable control of human activity intensity according to the leopard threshold response (0.14 times/day) may be beneficial to the distribution of most wildlife. This result will help to clarify the role of leopards as umbrella species in wildlife conservation. The study of ecological thresholds can provide reliable results for the development of scientific management policies for wildlife conservation.